The Effect of GCG on Company’s Value Mediated by CSR and Profitability on Banking Companies - Ardhi Aristo Alfarisi; Bambang Setyobudi Irianto; Negina Kencono Putri (Riset Akuntansi Keuangan, 2020)
The aim of the research was to analyze the effect of GCG on company’s value mediated by CSR and profitability. The independent variables was GCG; The mediating variable were CSR and profitability; while the dependent variable was company value. Banking companies listed in the Indonesia Stock Exchange in 2015-2017 were sampled. Purposive random sampling was applied to 120 sampled companies verified and simple linier regression analysis to test the hypothesis of the research. This research found that the GCG positively and significantly affect the CSR, CSR  positively and significantly affect the profitability, profitability positively and significantly affect the company value and GCG positively and significantly affect the company value.